2013
DOI: 10.1039/c3ta10940b
|View full text |Cite
|
Sign up to set email alerts
|

Titanium alkoxide induced BiOBr–Bi2WO6 mesoporous nanosheet composites with much enhanced photocatalytic activity

Abstract: Here we report a facile hydrothermal route for the preparation of BiOBr-Bi 2 WO 6 mesoporous nanosheet composites (MNCs) in the presence of titanium isopropoxide, Ti(O i Pr) 4 . High resolution transmission electron microscopy, X-ray diffraction, nitrogen adsorption/desorption analysis and X-ray photoelectron spectroscopy were employed for structural and composition analyses of the MNCs. The photogenerated charge transfer and photocatalytic activity of BiOBr-Bi 2 WO 6 MNCs were investigated by Kelvin probe for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…The Bi 2 WO 6 -based heterostructures with different morphologies were usually synthesized by hydrothermal method, for example, Fe 2 O 3 /Bi 2 WO 6 microspheres [7], Bi 2 O 3 /Bi 2 WO 6 rods [22], TiO 2 /Bi 2 WO 6 hollow tubes [23], BiOCl/Bi 2 WO 6 nanoflowers [24], and BiOBr/Bi 2 WO 6 microspheres [25], etc. But until now, few reports concerned with the photocatalytic activity of In 2 O 3 /Bi 2 WO 6 heterostructured microbelts synthesized by the electrospinning process.…”
Section: Introductionmentioning
confidence: 99%
“…The Bi 2 WO 6 -based heterostructures with different morphologies were usually synthesized by hydrothermal method, for example, Fe 2 O 3 /Bi 2 WO 6 microspheres [7], Bi 2 O 3 /Bi 2 WO 6 rods [22], TiO 2 /Bi 2 WO 6 hollow tubes [23], BiOCl/Bi 2 WO 6 nanoflowers [24], and BiOBr/Bi 2 WO 6 microspheres [25], etc. But until now, few reports concerned with the photocatalytic activity of In 2 O 3 /Bi 2 WO 6 heterostructured microbelts synthesized by the electrospinning process.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is to synthesize pure BiOBr with various architectures, such as lamellas, hierarchical microspheres, microflowers, mesoporous microspheres, and self-assembled 3-D architectures [10][11][12][13][14]. Another alternative is relevant to the fabrication of BiOBr hybrids with other semiconductors of suitable energy-band structures and the obtained hybrids normally own unique optical and catalytic properties, thanking to the formation of a positive synergistic effect between these ingredients [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the visible-light have shown that the preparation of composites of Bi 2 WO 6 with other semiconductors greatly improves the photocatalytic activity observed by promoting the separation of the photo-produced electron and hole such as for reported systems of Bi 2 WO 6 /BiOBr [15], Bi 2 WO 6 /TiO 2 [16] and Bi 2 O 3 /Bi 2 WO 6 [17].…”
Section: Introductionmentioning
confidence: 98%